Simulating the approach-retract phenomenon of AFM in virtual environment with haptic interface. Issue 5 (2nd September 2016) - Liu, Ke; Peng, Xiaobo
ABSTRACT: Atomic Force Microscope (AFM) is a crucial technique to study nanotechnology. The virtual reality simulation presented in this paper could be used to teach students or train professional researchers on approach-retract (AR) phenomenon. Based on different Hamaker constants and surface energies from various sample materials (mica, gold, and silicon nitride), various analytical force models of AR phenomenon were developed. The force models were simulated in the virtual environment using haptic device. Students were asked to complete surveys to examine the role of this simulation in the understanding of AFM. Results showed that students' perceptions of nanoscale phenomenon have been improved after using the simulation. GRAPHICAL ABSTRACT: